2021
DOI: 10.1111/scd.12567
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral health educational interventions on oral health of visually impaired school children: A systematic review and meta‐analysis

Abstract: Aim: To evaluate the effect of newer and traditional oral health education (OHE) methods in improving oral health knowledge, oral hygiene status and practices, plaque, gingival, and dental caries status of visually impaired children. Methodology: Comprehensive literature search was performed by using PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Web of Science, Google scholar, and Open Gray from 2010 to 2020 for studies in English language. Two reviewers critically assessed the studies for el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…48 For this reason, further research is therefore needed. However, like other authors [46][47][48] we believe that people with visual impairments should receive oral hygiene education based on the expertise of the dental professional, considering the needs and preferences of the individual and their caregivers.…”
Section: Assess the Use Of Auxiliary Methods And Tools According To T...mentioning
confidence: 62%
See 1 more Smart Citation
“…48 For this reason, further research is therefore needed. However, like other authors [46][47][48] we believe that people with visual impairments should receive oral hygiene education based on the expertise of the dental professional, considering the needs and preferences of the individual and their caregivers.…”
Section: Assess the Use Of Auxiliary Methods And Tools According To T...mentioning
confidence: 62%
“…Table 1 shows the protocol for the promotion of oral health care in people with visual impairment. At present, as two recent systematic reviews about oral health education in patients with visual impairment 46,47 indicate, there is no evidence about which method of dental hygiene and which oral health interventions are best for these patients. As well as on the benefits of these oral hygiene techniques on oral health.…”
Section: Assess the Use Of Auxiliary Methods And Tools According To T...mentioning
confidence: 99%
“…Systematic review conducted by Bhor K et al . (2020)[ 32 ] concluded that newer OHE methods (Braille, ATP) showed short-term improvement in oral hygiene behavior. However, evidence of this review is limited because OHE methods were evaluated over a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand whether or not PBL methods are superior to traditional teaching methods in oral radiology among dental students, well-designed long-term randomized controlled trials are needed. This study was planned with a systematic review and a meta-analysis as these are both highly effective at analysing studies conducted on similar topics [ 31 , 32 ]. Systematic reviews are efficient in quality evaluation of studies, while a meta-analysis is an objective method to carry out statistical analysis of various studies depending on their quality.…”
Section: Discussionmentioning
confidence: 99%